Fluid mechanics - Douglas, John F. (New Delhi : Prentice-Hall of India, 2017)
This work comprehensively covers the statics and dynamics of liquids and gases. Broad-based, it takes an applications-led approach, treating fluid mechanics as a truly cross-disciplinary topic.
Includes bibliographical references and index.
Keywords: Fluid mechanics